2014
DOI: 10.1038/mtna.2014.9
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing VDAC1 Expression by siRNA Inhibits Cancer Cell Proliferation and Tumor Growth In Vivo

Abstract: Alterations in cellular metabolism and bioenergetics are vital for cancer cell growth and motility. Here, the role of the mitochondrial protein voltage-dependent anion channel (VDAC1), a master gatekeeper regulating the flux of metabolites and ions between mitochondria and the cytoplasm, in regulating the growth of several cancer cell lines was investigated by silencing VDAC1 expression using small interfering RNA (siRNA). A single siRNA specific to the human VDAC1 sequence at nanomolar concentrations led to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 53 publications
(70 reference statements)
7
145
0
Order By: Relevance
“…Previous studies using a similar or the same ATP assay as applied in our study showed that VDAC1 downregulation leads to reduced levels of intracellular ATP (45,46,82). This observation is quite remarkable since this assay does not distinguish between mitochondrial or cytosolic ATP levels, indicating that blocking VDAC1 will reduce both ATP pools.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies using a similar or the same ATP assay as applied in our study showed that VDAC1 downregulation leads to reduced levels of intracellular ATP (45,46,82). This observation is quite remarkable since this assay does not distinguish between mitochondrial or cytosolic ATP levels, indicating that blocking VDAC1 will reduce both ATP pools.…”
Section: Discussionsupporting
confidence: 53%
“…There are numerous reports, however, that VDAC1 downregulation profoundly decreases levels of intra-and extracellular (secreted) ATP (45,46,82). Based on our observation that ceramide depletion decreases complex formation between tubulin and VDAC1, we tested if reducing ceramide will up-regulate cellular ATP levels.…”
Section: Downloaded Frommentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the cancer-associated abnormalities in glucose metabolism enhance cellular resistance to apoptosis, with mitochondria being found to play a key role in this process [275][276][277][278][279]. Lung cancer tumors and cell lines Up-regulation Western blot Tumor and healthy tissues from the same patient were compared [421] The high glycolytic rate that is characteristic of hypoxic solid tumors is attributed to marked over-expression of mitochondrial-bound HK that is considered the rate-limiting enzyme of glycolysis [2,[280][281][282]. HK likely plays a key role in cell growth rate and survival of cancer cells and is probably a major factor underlying the Warburg effect [273,281,[283][284][285].…”
Section: Reprogramming Energy Metabolism In Cancer and The Warburg Efmentioning
confidence: 99%
“…It has also been shown that VDAC1 silencing potentiated H 2 O 2 -induced apoptosis and impaired mitochondrial Ca 2+ loading, while silencing VDAC2 had the opposite effects [261]. Furthermore, a single siRNA specific to the human VDAC1 sequence (hVDAC1-siRNA) was shown to silence VDAC1 expression by over 90% at low nanomolar concentrations and inhibit the growth of various cancer cell types, both in vitro and in vivo [421]. In a xenograft lung cancer mouse model, chemically modified VDAC1-siRNA not only inhibited tumor growth but also resulted in tumor regression [421].…”
Section: Vdac1-depletion Using Rnaimentioning
confidence: 99%